Polyelectrolyte material and application thereof

By designing and synthesizing AEM polymers with a series of biphenyl block structures, the problems of insufficient stability and poor solubility of existing AEM film materials under high temperature and alkaline conditions are solved, and high-efficiency and low-energy consumption film preparation and mechanical strength are achieved.

CN119638929APending Publication Date: 2025-03-18GUANGDONG MINGYANG TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411735323.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing polyaryl-piperidine (AEM) film materials are insufficient in stability and poor solubility under high temperature alkaline conditions, resulting in low film making efficiency and high energy consumption.

Method used

Design a synthetic series of AEM polymers with biphenyl block structures to improve the solubility and mechanical strength of the polymer by controlling the solubility of biphenyls, and improve yield through specific synthesis processes.

Benefits of technology

It realizes the stability under high temperature alkaline conditions, while improving the solubility and mechanical strength of the polymer, and is suitable for the manufacturing of scraping and film electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638929A_ABST
    Figure CN119638929A_ABST
Patent Text Reader

Abstract

The invention discloses a polyelectrolyte material. The polyelectrolyte material comprises a poly (aryl-alkylene) main chain; the main chain does not contain heteroatoms such as sulfur, ether and oxygen, so that the phenomenon that unstable electron-rich sites are generated on aryl due to the electron donating effect of the heteroatoms is avoided, and hydroxyl radicals are not prone to attacking the poly (aryl-alkylene) polymer; by using a high-stability cation exchange group, the alkali resistance is improved. The dissolvability of the polymer is controlled through the dissolvability of biphenyl, the mechanical strength of the polymer is increased by the biphenyl block structure unit, the dissolvability of the polymer is increased while the strength of the polymer is ensured, and the polymer can be dissolved in methanol or methanol / water after being soaked in sodium chloride; the method is suitable for blade coating method membrane preparation and membrane electrode manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of organic membrane materials, and in particular to a polyelectrolyte material and application thereof. Background Art

[0002] The polymer microstructure of anion exchange membrane (AEM) is composed of a polymer backbone and anion exchange functional groups. The functional groups are usually quaternary ammonium salts and phosphorus cation groups, which can be connected to the main chain or the extended side chain of the main chain. Quaternary ammonium salt functional groups generally include: quaternary ammonium, heterocyclic system, guanidine system, phosphorus system, sulfonated type and metal-based system. Marino MG et al. (ChemSusChem, 2015, 8 (3): 513-523.) studied the stability of cationic groups under alkaline conditions. According to the difficulty of synthesis and economic cost, trimethylamine, piperidine and specially substituted imidazole cationic groups are the most promising anion exchange functional groups for commercial AEM. For example, N, N-dimethylpiperidine (DMP) and 6-azo-spiro[5.5]undecane (ASU) cations show particularly high alkaline stability.

[0003] Commonly used AEM polymer skeletons include polyarylene ether, polystyrene, polyethylene, polystyrene and polyvinyl alcohol. Generally, in the AEM polymer skeleton, polymers containing heteroatoms are easy to degrade, and polymers connected by CC atoms have higher alkali resistance and stability.

[0004] At present, poly (aryl-piperidine) (PAP) is a more mainstream AEM membrane material on the market, mainly because of its rigid aromatic backbone, high alkaline stability, tunable structure and relative ease of synthesis. Commercially available N-methyl-4-piperidone monomers and different aromatic hydrocarbons are directly synthesized into high molecular weight polymers through superacid reactions, and then appropriate quaternization reactions are carried out to introduce the desired piperidine type. Membranes based on medium ion exchange capacity PAP have good water absorption, high hydroxide ion conductivity and chemical stability. For example, AEMs based on poly (p-triphenyldimethylpiperidine) showed no structural changes when stored in 2M sodium hydroxide at 60°C for 15 days. The alkaline stability of AEMs based on PAP has been confirmed to be stable for more than 1500 hours under 1M sodium hydroxide at 80°C.

[0005] Another type of commercial AEM structure on the market is a poly(aryl-alkylene) polymer directly synthesized from trifluoroalkyl ketone monomers and different aromatic hydrocarbons through superacid reaction (Bae et al. ACS Macro Lett. 2015, 4, 814-818). CN114025957A and CN112940226A also disclose similar poly(aryl-alkylene) polymers, which have alkaline stable cations such as trimethylamine and imidazolium introduced into the rigid aromatic polymer backbone without ether bonds.

[0006] The casting method is generally used to prepare ion membrane materials using polyaryl resins. However, the main chain structural units of the polyaryl resins are relatively rigid, resulting in poor polymer solubility. They are only soluble in two high-boiling point solvents, DMSO / NMP, and slightly soluble in DMF. The boiling points of both DMSO / NMP solvents are above 180°C, and the traditional blade coating film drying time is too long and the efficiency is low. The main chain structural units of polyaryl AEM are relatively rigid and difficult to dissolve in low-boiling point solvents such as ethanol. The energy consumption of casting films using high-boiling point solvents such as DMSO is also too high. Summary of the invention

[0007] The purpose of the present invention is to overcome at least one of the shortcomings of the prior art and provide a polyelectrolyte material and its application

[0008] The technical solution adopted by the present invention is:

[0009] In a first aspect, the present invention provides a polyelectrolyte material, characterized in that the polyelectrolyte material has the following structural units:

[0010] 1) The structural unit shown in the structure of the following formula 1A: 2) The structural unit shown in the following formula 2A: 3) Optional structural units represented by the following formula 3A, 3B, 3C or 3D: In the formula, m represents an integer between 1 and 20; n represents an integer between 0 and 5; b represents an integer between 0 and 5; the R1 group is independently oxygen, nitrogen, sulfur, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with fluoride; the R 200 , R 210 , R 220 The groups are each independently hydrogen, fluorine, fluoride, alkyl, cycloalkyl, alkenyl, alkynyl or aryl, and the alkyl, cycloalkyl, alkenyl, alkynyl or aryl is optionally substituted with fluoride; the R 100 The group is hydrogen, fluoride, alkyl, cycloalkyl, alkenyl, alkynyl, aryl or a cation exchange group and the alkyl, cycloalkyl, alkenyl, alkynyl or aryl is optionally substituted with fluoride; the R 20 , R 30 , R 40 , R 50 , R 60 , R 70 , R 80 and R 90 The groups are each independently hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide, and wherein R 30 and R 60A five-membered ring or a six-membered ring optionally connected to a halide or alkyl-substituted ring; the R2 group is independently hydrogen, fluoride, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with fluoride; the R group is independently alkyl, alkenyl, alkynyl or a substituent having the following formula 4B, and the alkyl, alkenyl, alkynyl or a substituent having the formula 4B is optionally substituted with a halide or a cation exchange group;

[0011] The R 110 , R 120 , R 130 , R 140 and R 150 The groups are each independently hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide;

[0012] The R3 and R4 groups are each independently hydrogen, fluoride, alkyl, alkenyl, alkynyl, aryl or cation exchange group, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with fluoride;

[0013] The R5 group is an alkyl group, an alkenyl group or an alkynyl group, and the alkyl group, the alkenyl group or the alkynyl group is optionally substituted by a halide group or a cation exchange group.

[0014] In some examples, the synthesis method of the structural unit shown in Formula 2A includes the following steps: dissolving the aromatic hydrocarbon raw material in dichloromethane, stirring and cooling to -5 to 0°C, adding TFSA solution; slowly adding the monomer of the structural formula 3 and reacting for 2 to 72 hours;

[0015] The structural monomer shown in formula 3 is:

[0016] The aromatic hydrocarbon raw material is selected from the following structures:

[0017] n represents an integer between 0 and 5; 20 , R 30 , R 40 , R 50 , R 60 , R 70 , R 80 and R 90 The groups are each independently hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide, and wherein R 30 and R 60 an optionally attached halide or alkyl substituted five- or six-membered ring;

[0018] The R groups are independently alkyl, alkenyl, alkynyl or a substituent having the following formula 4B, and the alkyl, alkenyl, alkynyl or a substituent having the following formula 4B is optionally substituted with a halide or a cation exchange group;

[0019]

[0020] The R 110 , R 120 , R 130 , R 140 and R 150 Each group is independently hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide.

[0021] In some examples, the molar ratio of the aromatic hydrocarbon raw material to the total amount of the monomer of formula 3 is 2 to 10.

[0022] In some examples, the molar amount of the monomer of formula 3 added per hour is 0.2 to 1 part of the total amount of the aromatic hydrocarbon raw materials added.

[0023] In some examples, the aromatic hydrocarbon feedstock includes, but is not limited to:

[0024]

[0025]

[0026] In some examples, the method for synthesizing the monomer of formula 2A can be selected from the following:

[0027] (1) For example: In a 50 ml single-necked flask, 7.7 g (5 eq) of biphenyl is dissolved in 10 ml of DCM, stirred and cooled to 0°C, and TFSA (7.96 ml) is slowly added dropwise under temperature control; 1.26 g (1 eq) of trifluorobutanone is slowly added dropwise (the addition time is about 2 h), and after the addition is completed, the reaction is carried out at 0°C for 4 h.

[0028] After the reaction was completed, methanol-water solution (1 / 1) was added, the aqueous phase was extracted once with DCM, and the organic phase was washed twice with saturated sodium bicarbonate solution and dried over anhydrous sodium sulfate. After treatment, column chromatography was performed to obtain 3.12 g of the product with a yield of about 75.2% (named QBPAF).

[0029]

[0030] (2) As an example, another method for synthesizing a monomer of formula 2A (named QTPAF) is provided, similar to QBPAF:

[0031]

[0032] (3) As an example, another synthesis method of a monomer of formula 2A (named QmTPAF) is provided, similar to QBPAF:

[0033]

[0034] (4) As an example, another synthesis method of a monomer of formula 2A (named QBPHF) is provided, which is similar to QBPAF:

[0035]

[0036] (5) As another example, in other cases, a monomer having the structural formula 2A can be synthesized by reference to similar or other methods.

[0037] In some examples, the synthesis method of the monomers of formula 3A, 3B, 3C, and 3D can be selected from the following:

[0038] 1) To synthesize ketone monomer 5-bromo-1,1,1-trifluoromethyl-2-ketone, dissolve 4-bromobutyric acid (167 g, 1 mol, 1 eq) in toluene (400 ml) in a 5000 ml three-necked flask, slowly add trifluoroacetic anhydride (778.4 ml, 5.6 mol, 5.58 eq) under ice bath stirring, cool to 0°C and then drop pyridine (650 mL, 8 mol, 8 eq). After the addition is complete, the temperature rises to 50°C and reacts for 48 h under nitrogen. Then, the temperature is lowered to 0°C, 1430 ml of deionized water is added dropwise, and the temperature is raised to 45°C for reaction for 2 h.

[0039] After the reaction was completed, the layers were separated and the organic layer was extracted with ethyl acetate (4*1250 ml). The organic phase was washed with deionized water, saturated sodium carbonate, and saturated sodium chloride solution in sequence, and then dried with anhydrous sodium sulfate. The solvent was then evaporated and separated with a chromatographic column to obtain a light brown crystalline product 5-bromo-1,1,1-trifluoromethyl-2-one (3A) (65.4 g, yield of about 30%). The synthesis equation is shown below.

[0040]

[0041] 2) As another example, another synthesis method is provided:

[0042] The bromoalkylated trifluoroacetophenone monomer was obtained by Friedel-Craft acylation. Dichloromethane (300 mL) was added to a flask, and 0.22 mol of aluminum chloride was added, and the stirring was controlled below 5°C. Trifluoroacetic anhydride (0.13 mol) was placed in a flask and stirred for 15 min. The diluted 1-bromo-3-phenylpropane (0.1 mol, 50 mL of dichloromethane) solution was added dropwise. After the addition was completed, the reaction was carried out at 0°C for 16 hours. When the reaction was complete, the mixture was poured into ice water, extracted with ether, and then evaporated. The 120-125°C fraction was collected by vacuum distillation to obtain 26.6 g (90% yield) of a transparent yellow liquid.

[0043]

[0044] 3) As another example, another synthesis method is provided:

[0045] A mixture of K2CO3 (23.0 g, 166.6 mmol), 1,5-diiodopentane (53.83 g, 166.6 mmol) and 4-piperidone hydrobromide (10 g, 55.5 mmol) was stirred in 500 mL of acetone for 24 hours. The solvent was then rotary evaporated, and the crude product was then diluted with 300 mL of acetonitrile and heated at 70°C for 15 hours to obtain solid 3-oxo-6-azaspiro[5.5]undecane bromide monomer.

[0046] The product was filtered and dried in vacuo.

[0047]

[0048] 4) As another example, another synthesis method is provided:

[0049] A mixture of K2CO3 (23.0 g, 166.6 mmol), 1,4-diiodobutane (51.63 g, 166.6 mmol) and 4-piperidone hydrobromide (10 g, 55.5 mmol) was stirred in 500 mL of acetone for 24 hours. The solvent was then rotary evaporated, and the crude product was then diluted with 300 mL of acetonitrile and heated at 70°C for 15 hours to obtain a solid nitrogen bromide spiro salt monomer. The product was filtered and dried in vacuo.

[0050]

[0051] X - Anion: Br - ,I - , Cl - OH - 、HCO3 - wait.

[0052] 5) As another example, another synthesis method is provided:

[0053] 1,10-Dibromodecane (33 g, 110.0 mmol) was added to a mixture of 4-piperidone hydrobromide (5 g, 27.8 mmol), K2CO3 (7.7 g, 55.8 mmol) in acetone, and then the mixture was stirred overnight at room temperature. The solvent was removed, and the residue was subjected to column chromatography to give 5.0 g (56.5%) of the product.

[0054]

[0055] In some examples, the cation exchange group has the following structure:

[0056]

[0057] Among them, R 11 and R 12 The groups are each independently alkylene; R6, R7, R8, R9 and R 10 The groups are each independently alkyl, alkenyl, aryl or alkynyl; a is 0, 1, 2, 3, 4, 5 or 6; Z is an N element or a P element;

[0058] The R' group is a nitrogen-containing heterocycle selected from substituted pyrrole, pyrroline, pyrazole, pyrazoline, imidazole, imidazoline, triazole, pyridine, triazine, pyrazine, pyridazine, pyrimidine, azepine, quinoline, piperidine, pyrrolidine, pyrazolidine, imidazolidine, azepane, isoxazole, isoxazoline, oxazole, oxazoline, oxadiazole, oxatriazole, dioxazole, oxazine, oxadiazine, isoxazolidine, morpholine, thiazole, isothiazole, oxathiazole, oxathiazine or caprolactam, wherein each substituent is independently alkyl, alkenyl, alkynyl, aryl or aralkyl.

[0059] In some examples, the R' group is a structure shown in Formula 4A: Where: R 14 , R 15 , R 16 and R 17 Each group is independently hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide.

[0060] In some examples, the R' group has a structure shown in Formula 5 or Formula 5B below:

[0061]

[0062] In some examples, the synthesis method of the cation exchange group can be selected from the following:

[0063] 1) As an example: Z is N, a is 0, R6, R7, R8 are methyl, R 12 It is hexamethylene and named (MQN).

[0064] Synthesis of MQN-Br. A mixture of THF (100 ml) and trimethylamine ethanol solution (1 eq) was added dropwise to a solution of 1,6-dibromohexane (0.15 mol, 5 eq) in THF (200 ml). After the addition, the mixture was stirred for 24 h. A white solid was slowly formed. The white precipitate was filtered and washed with cold THF. After vacuum drying, MQN-Br (90% yield) was obtained as a white or light yellow powder.

[0065]

[0066] 2) As another example: Z is N, a is 1, R6, R7, R8 are methyl, R 11 , R 12 It is hexamethylene and named (PMDA).

[0067] Synthesize pentamethyldiammonium side chain (PMDA).Under mechanical stirring, at 0 ℃ in 1h, THF (20ml) solution of MeI (2.9ml, 0.047mol) was added dropwise to N, N, N', N'-tetramethyl-1,6-hexanediamine (50ml, 0.235mmol) and THF (100ml).Then, continue to react for 24h at this temperature.Filter the slurry with white precipitate and wash with cold THF.N, N, N, N', N'-pentamethyl-1-amino-six-6-ammonium iodide (PMDA-I) is dried in vacuo and collected, 90% yield.

[0068]

[0069] 3) As an example: Z is N, a is 0, R 12 is hexamethylene, R′ is imidazolium of (Formula 5), ​​named (IM).

[0070] Synthesis of IM-Br. A mixture of THF (100 ml) and 1-butyl-2-mesityl-4,5-dimethyl-1H-imidazole (1 eq) was added dropwise to a THF (200 ml) solution of 1,6-dibromohexane (0.15 mol, 5 eq). After addition, the mixture was stirred for 24 h. A white solid was slowly formed. The white precipitate was filtered and washed with cold THF. After vacuum drying, IM-Br (90% yield) was obtained as a white or light yellow powder.

[0071]

[0072] 4) As an example: Z is N, a is 0, R12 is hexylene, R' is imidazolium of (Formula 5B), and is named (PHIM).

[0073] Synthesis of PHIM-Br. A mixture of THF (100 ml) and 1-butyl-2-mesityl-4,5-diphenyl-1H-imidazole (1 eq) was added dropwise to a THF (200 ml) solution of 1,6-dibromohexane (0.15 mol, 5 eq). After addition, the mixture was stirred for 24 h. A white solid was slowly formed. The white precipitate was filtered and washed with cold THF. After vacuum drying, PHIM-Br (90% yield) was obtained as a white or light yellow powder.

[0074]

[0075] In some examples, the X - For the anion Br - ,I - , Cl - OH - or HCO3 - .

[0076] In some examples, the preparation method of the polyelectrolyte material is: a monomer of the structural unit of formula 1A, a monomer of the structural unit of formula 2A, and a monomer of the structure shown in formula 3 are subjected to a superacid FC reaction in the presence of a catalyst to obtain a first intermediate polymer, and the first intermediate polymer is subjected to an alkylation reaction to obtain the polyelectrolyte material.

[0077] For example:

[0078] Step 1: Dissolve the monomer of formula 1A and optional monomer of formula 2A (total 0.1 mol), and optional monomer of formula 3 (0.13 mol) in 60 ml DCM, cool to 0°C with an ice bath, add TFSA (79.6 ml, 0.9 mol) dropwise, and polymerize under ice bath conditions for 2h-12d after the addition is complete. After the reaction is complete, add DMSO and NMP to quench and dissolve the polymer, sink it into the solvent to obtain a white solid, rinse it repeatedly with deionized water several times, and then dry it in a vacuum at 80°C for 12h.

[0079] Step 2: synthesize quaternary ammonium salt, dissolve the dried white solid in the previous step with a polar solvent (NMP, DMF, DMSO, DMAc, etc.), quickly add quaternary ammonium or phosphonium compound or nitrogen-containing heterocycle or alkylating agent to carry out alkylation reaction for more than 12 hours, precipitate and filter with solvent to obtain a light yellow solid, wash with distilled water and dry.

[0080] The catalyst is trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, heptafluoro-1-propanesulfonic acid, trifluoroacetic acid, perfluoropropionic acid, heptafluorobutyric acid or a combination thereof.

[0081] The solvent in step 1 includes but is not limited to dichloromethane, dichloroethane, trifluoroacetic acid, trifluoromethanesulfonic acid, chloroform, 1,1,2,2-tetrachloroethane, dimethylacetamide or a combination thereof.

[0082] The precipitation solvent in step 1 includes but is not limited to water, methanol, ethanol, propanol, isopropanol, butanol, isobutanol, amyl alcohol, tetrahydrofuran or a combination thereof.

[0083] The precipitation solvent in step 2 includes but is not limited to water, ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate or a combination thereof.

[0084] The alkylating agent includes but is not limited to methyl iodide, ethyl iodide, 1-iodopropane, 1-iodobutane, 1-iodopentane, 1-iodohexane, 1,10-dibromodecane, methyl bromide, ethyl bromide, 1-bromopropane, 1-bromobutane, 1-bromopentane, 1-bromohexane, methyl chloride, ethyl chloride, 1-chloropropane, 1-chlorobutane, 1-chloropentane, 1-chlorohexane, methyl trifluoromethanesulfonate, methyl methanesulfonate, methyl fluorosulfonate, 1,2-dimethylhydrazine, trimethyl phosphate, dimethyl sulfate or a combination thereof.

[0085] In a second aspect, the present invention provides an anion exchange membrane, which is formed by dissolving the polyelectrolyte material described in the first aspect in a polar solvent, casting it on a substrate, and exchanging it with anions.

[0086] In some examples, the ion exchange membrane can be prepared by a method comprising:

[0087] The anion exchange polymer can be made into a uniform anion exchange membrane. After washing with distilled water, the polymer is filtered to obtain a light yellow powder. The obtained polymer is vacuum dried at 80°C for 24 hours, dissolved in a polar solvent (NMP, DMF, DMSO, DMAc, etc.), centrifuged, cast on a substrate, dried at 60-100°C for 5-24 hours to form a membrane, and then vacuum dried at 80-150°C for 5-24 hours. The thickness of the membrane is between 10 and 100 μm. More preferably, the thickness of the membrane is 30-50 μm.

[0088] The uniform anion exchange membrane substrate includes but is not limited to stainless steel plate, glass, PET plate, PP plate, PEN and the like.

[0089] The anion exchange polymer can be made into an enhanced anion exchange membrane. Such an enhanced anion exchange membrane can be prepared by methods including but not limited to the following: wetting a porous substrate in a liquid to form a wetted substrate; dissolving a poly(aryl-piperidine) polymer in a solvent to form a uniform solution; applying the solution to the wetted substrate to form the enhanced membrane; and drying the enhanced membrane. Any known membrane forming technique, such as casting, spraying, impregnation or doctoring to the wetted substrate can be used. If necessary, the enhanced membrane can be impregnated multiple times with the poly(aryl-alkylene) polymer by re-wetting the enhanced membrane and repeating the dissolving, casting and drying steps.

[0090] The reinforced substrate includes but is not limited to PPS, PEK, PET, porous polytetrafluoroethylene, porous polyvinylidene fluoride, steel belt, polypropylene, polyethylene, glass fiber cloth, etc.

[0091] The liquid used to wet the porous substrate may be a low boiling point solvent, such as a lower alcohol (eg, methanol, ethanol, propanol, isopropanol) or water. Preferably, the liquid is anhydrous ethanol.

[0092] The thickness of the porous substrate may be 1 μm to 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100 μm. Preferably, the thickness of the porous substrate is 5 to 30 μm, or 7 to 20 μm.

[0093] The beneficial effects of the present invention are:

[0094] A series of biphenyl block structure AEM polymers are designed and synthesized; the solubility of the polymer is controlled by the solubility of biphenyl; the biphenyl block structural unit increases the mechanical strength of the polymer, ensuring the strength of the polymer while increasing the solubility of the polymer; the polymer can be dissolved in methanol or methanol / water after being soaked in sodium chloride; it can be applied to the manufacture of membranes by blade coating and membrane electrodes.

[0095] Compared with the poly (aryl-piperidine) polymer of CN118546339A, the aromatic structure monomer of formula (2A) in this article is more difficult to synthesize and has a lower yield, which is manifested in that the synthesis process of the aromatic structure of formula (2A) is a polymer polymerization process, which will produce a block structure with a higher molecular weight. In order to increase the yield, the present invention increases the molar mass of aromatic hydrocarbons to ensure that no polymer polymerization reaction occurs, and its yield can easily reach more than 70%. BRIEF DESCRIPTION OF THE DRAWINGS

[0096] Figure 1 The QBPAF prepared in Example 1 1 H NMR spectra.

[0097] Figure 2 This is the MS spectrum of QBPAF prepared in Example 1. DETAILED DESCRIPTION

[0098] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.

[0099] Example 1

[0100] In this embodiment, the synthesis method of QBPAF is as follows:

[0101] In a 50 ml single-necked flask, 7.7 g (5 eq) of biphenyl was dissolved in 10 ml of DCM, and the temperature was cooled to 0°C with stirring. TFSA (7.96 ml) was slowly added dropwise under temperature control; 1.26 g (1 eq) of trifluorobutanone was slowly added dropwise (the addition time was about 2 h). After the addition was completed, the mixture was reacted at 0°C for 4 h.

[0102] After the reaction was completed, methanol aqueous solution (1 / 1) was added, the liquid was separated, the aqueous phase was extracted once with DCM, and the organic phase was washed twice with saturated sodium bicarbonate solution. Drying with anhydrous sodium sulfate. After treatment, column chromatography was performed to obtain 3.12 g of the product, with a yield of about 75.2%. 1 H NMR and MS spectra are shown in Figure 1 and Figure 2 .

[0103]

[0104] Then, 1-bromo-3-phenylpropane, trifluoroacetophenone and QBPAF (named QBPAF-1-x , wherein x is the molar ratio of 1-bromo-3-phenylpropane to trifluoroacetophenone, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out by the following three main steps QBPAF-1-x :(1) Synthesis of poly(aryl-alkylene) polymer, (2) Synthesis of alkylated polymer, (3) Forging membrane and hydroxide ion exchange. The synthesis equation is as follows:

[0105]

[0106] (1) Synthesis of poly(aryl-alkylene) polymers containing active sites. In a 250 mL three-necked flask equipped with an overhead mechanical stirrer, 1-bromo-3-phenylpropane (16.93 g, 0.085 mol), QBPAF (6.24 g, 0.015 mol) and 2,2,2-trifluoroacetophenone (45.24 g, 0.13 mol) were dissolved in dichloromethane (30 mL) and trifluoromethanesulfonic acid (TFSA) (106 mL) was added dropwise at 0°C over 30 minutes. Thereafter, the reaction was continued at this temperature for 4 to 48 hours. The resulting viscous dark green solution was slowly poured into an ethanol-water solution. The white fibrous solid was filtered, washed with water and immersed in 1 M sodium hydroxide for 12 hours at room temperature. Finally, the white fibrous product was filtered, washed with water and dried under vacuum at 80°C for 12 hours. The yield of the polymer was 97%.

[0107] (2) Synthetic alkylated polymer (QBPAF-1-85) . In a 50 mL single-necked flask equipped with magnetic stirring, the active site-containing polymer (1.0 g) was dissolved in 1-methyl-2-pyrrolidone (20 mL). Trimethylamine (1 g) was quickly added. The solution was stirred at room temperature for 12 hours. The resulting viscous yellow solution was added dropwise to diethyl ether. The yellow solid was filtered, washed with diethyl ether and dried completely under vacuum at 60 °C. Polymer QBPAF-1-85 The yield is almost 100%.

[0108] (3) QBPAF-1-85 forged membrane and hydroxide ion exchange By QBPAF-1-85 The polymer (1.0 g) was dissolved in NMP (20 mL), cast on a glass plate or a stainless steel plate, dried at 60-100°C for 5-24 hours to form a membrane, and then vacuum dried at 80-150°C for 5-24 hours. The membrane thickness was between 10 and 100 μm. The membrane (in the form of bromide) was peeled off from the glass plate in contact with deionized water. The membrane was subjected to hydroxide ion exchange in a 1M sodium hydroxide solution at 80°C to obtain an anion exchange membrane in the form of hydroxide. Others were prepared by different molar ratios of 1-bromo-3-phenylpropane and trifluoroacetophenone. QBPAF-1-x membrane.

[0109] Example 2

[0110] Poly(aryl-alkylene) was prepared from 1-bromo-3-phenylpropane, trifluoroacetophenone and QmTPAF (named QmTPAF-2-x, where x is the molar ratio of 1-bromo-3-phenylpropane to trifluoroacetophenone, which is 1 to 100). The preparation was carried out through the following three main steps: QmTPAF-2-x :(1) Synthesis of poly(aryl-alkylene) polymer, (2) Synthesis of alkylated polymer, (3) Forging membrane and hydroxide ion exchange. The structural formula is as follows:

[0111]

[0112] (1) Synthesis of poly(aryl-alkylene) polymers containing active sites . In a 250 mL three-necked flask equipped with an overhead mechanical stirrer, 1-bromo-3-phenylpropane (17.91 g, 0.09 mol), QmTPAF (5.68 g, 0.01 mol) and 2,2,2-trifluoroacetophenone (45.24 g, 0.13 mol) were dissolved in dichloromethane (30 mL) and trifluoromethanesulfonic acid (TFSA) (79.6 mL) was added dropwise at 0°C over 30 minutes. Thereafter, the reaction was continued at this temperature for 4 to 48 hours. The resulting viscous dark green solution was slowly poured into an ethanol-water solution. The white fibrous solid was filtered, washed with water and immersed in 1 M sodium hydroxide at room temperature for 12 hours. Finally, the white fibrous product was filtered, washed with water and dried under vacuum at 80°C for 12 hours. The yield of the polymer was 97%.

[0113] (2) Synthetic alkylated polymer (QmTPAF-2-90) . In a 50 mL single-necked flask equipped with magnetic stirring, the active site-containing polymer (1.0 g) was dissolved in 1-methyl-2-pyrrolidone (20 mL). Trimethylamine (1 g) was quickly added. The solution was stirred at room temperature for 12 hours. The resulting viscous yellow solution was added dropwise to diethyl ether. The yellow solid was filtered, washed with diethyl ether and dried completely under vacuum at 60 °C. Polymer QmTPAF-2-90 The yield is almost 100%.

[0114] (3) QmTPAF-2-90 Forged Membrane and Hydroxide Ion Exchange . The QmTPAF-2-90 polymer (1.0 g) was dissolved in NMP (20 mL), cast on a glass plate or a stainless steel plate, dried at 60-100°C for 5-24 hours to form a membrane, and then vacuum dried at 80-150°C for 5-24 hours. The thickness of the membrane was between 10 and 100 μm. The diaphragm (in the form of bromide) was peeled off from the glass plate in contact with deionized water. The membrane was subjected to hydroxide ion exchange in a 1 M sodium hydroxide solution at 80°C to obtain an anion exchange membrane in the form of hydroxide. Others were prepared by different molar ratios of 1-bromo-3-phenylpropane and trifluoroacetophenone. QmTPAF-2-x membrane.

[0115] Example 3

[0116] The product is composed of 1-bromo-3-phenylpropane, N-methyl-4-piperidone and QBPAF (named QBPAF-3-x , wherein x is the molar ratio of 1-bromo-3-phenylpropane to N-methyl-4-piperidone, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out by the following three main steps QBPAF-3-x :(1) Synthesis of poly(aryl-alkylene) polymer, (2) Synthesis of alkylated polymer, (3) Forging membrane and hydroxide ion exchange. The structural formula is as follows:

[0117]

[0118] (1) Synthesis of poly(aryl-alkylene) polymers containing active sites . In a 250 mL three-necked flask equipped with an overhead mechanical stirrer, 1-bromo-3-phenylpropane (79.6 g, 0.04 mol), QBPAF (6.24 g, 0.06 mol) and N-methyl-4-piperidone (14.84 g, 0.13 mol) were dissolved in dichloromethane (30 mL) and trifluoromethanesulfonic acid (TFSA) (79.6 mL) was added dropwise at 0°C over 30 minutes. Thereafter, the reaction was continued at this temperature for 4 to 48 hours. The resulting viscous dark green solution was slowly poured into an ethanol-water solution. The white fibrous solid was filtered, washed with water and immersed in 1 M sodium hydroxide for 12 hours at room temperature. Finally, the white fibrous product was filtered, washed with water and dried under vacuum at 80°C for 12 hours. The yield of the polymer was 97%.

[0119] (2) Synthetic alkylated polymer (QBPAF-3-40) . In a 50 mL single-necked flask equipped with magnetic stirring, the piperidine-functionalized polymer (1.0 g) was dissolved in 1-methyl-2-pyrrolidone (20 mL). Trimethylamine (1 g) was quickly added. The solution was stirred at room temperature for 12 hours. The resulting viscous yellow solution was added dropwise to diethyl ether. The yellow solid was filtered, washed with diethyl ether and dried completely under vacuum at 60 °C. The dried solid was dissolved in 1-methyl-2-pyrrolidone (20 mL) and iodomethane (1 g) was quickly added. The solution was stirred at room temperature for 12 hours. The resulting viscous yellow solution was added dropwise to diethyl ether. The yellow solid was filtered, washed with diethyl ether and dried completely under vacuum at 60 °C. Polymer QBPAF-3-40 The yield is almost 100%.

[0120] (3) QBPAF-3-40 forged membrane and hydroxide ion exchange By QBPAF-3-40 The polymer (1.0 g) was dissolved in NMP (20 mL), cast on a glass plate or a stainless steel plate, dried at 60-100°C for 5-24 hours to form a membrane, and then vacuum dried at 80-150°C for 5-24 hours. The membrane thickness was between 10 and 100 μm. The membrane (in the form of bromide or iodide) was peeled off from the glass plate in contact with deionized water. The membrane was subjected to hydroxide ion exchange in a 1M sodium hydroxide solution at 80°C to obtain an anion exchange membrane in the form of hydroxide. Others were prepared by different molar ratios of 1-bromo-3-phenylpropane and trifluoroacetophenone. QBPAF-3-x membrane.

[0121] Example 4

[0122] Poly(aryl-alkylene) was prepared from 4-phenyl-1-butyl bromide, trifluoroacetophenone and QBPAF (designated as QBPAF-4-x, where x is the molar ratio of 4-phenyl-1-butyl bromide to trifluoroacetophenone, which is 1 to 100). The preparation of QBPAF-4-x is similar to QBPAF-1-x by the following three major steps: (1) synthesis of poly(aryl-alkylene) polymer, (2) synthesis of alkylated polymer, and (3) membrane forging and hydroxide ion exchange. The structure is as follows:

[0123]

[0124] Example 5

[0125] Poly(aryl-alkylene) was prepared from 1-bromo-3-phenylpropane, trifluoroacetophenone and QBPHF (named QBPHF-5-x, where x is the molar ratio of 1-bromo-3-phenylpropane to trifluoroacetophenone, which is 1 to 100). The preparation of QBPHF-5-x is similar to QBPAF-1-x through the following three main steps: (1) synthesis of poly(aryl-alkylene) polymer, (2) synthesis of alkylated polymer, and (3) membrane forging and hydroxide ion exchange. The structural formula is as follows:

[0126]

[0127] Example 6

[0128] Poly(aryl-alkylene) was prepared from 1-bromo-3-phenylpropane, trifluoroacetophenone and QTPAF (named QTPAF-6-x, where x is the molar ratio of 1-bromo-3-phenylpropane to trifluoroacetophenone, which is 1 to 100). The preparation of QTPAF-6-x is similar to QBPAF-1-x by the following three main steps: (1) synthesis of poly(aryl-alkylene) polymer, (2) synthesis of alkylated polymer, and (3) membrane forging and hydroxide ion exchange. The structural formula is as follows:

[0129]

[0130] Example 7

[0131] The product is composed of trifluoromethoxybenzene, N-methyl-4-piperidone and QBPAF (named QBPAF-7-x , wherein x is the molar ratio of trifluoromethoxybenzene to N-methyl-4-piperidone, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out by the following three main steps QBPAF-7-x Similar to QBPAF-1-x: (1) synthesis of poly(aryl-alkylene) polymer, (2) synthesis of alkylated polymer, (3) membrane forging and hydroxide ion exchange. The structural formula is as follows:

[0132]

[0133] Example 8

[0134] The product is composed of trifluoromethoxybenzene, N-methyl-4-piperidone and QTPAF (named QTPAF-8-x , wherein x is the molar ratio of trifluoromethoxybenzene to N-methyl-4-piperidone, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out by the following three main steps QTPAF-8-x Similar to QBPAF-1-x: (1) synthesis of poly(aryl-alkylene) polymer, (2) synthesis of alkylated polymer, (3) membrane forging and hydroxide ion exchange. The structural formula is as follows:

[0135]

[0136] Example 9

[0137] Composed of dodecylbenzene, N-methyl-4-piperidone and QBPAF (named QBPAF-9-x , wherein x is the molar ratio of dodecylbenzene to N-methyl-4-piperidone, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out by the following three main steps QBPAF-9-x Similar to QBPAF-1-x: (1) synthesis of poly(aryl-alkylene) polymer, (2) synthesis of alkylated polymer, (3) membrane forging and hydroxide ion exchange. The structural formula is as follows:

[0138]

[0139] Example 10

[0140] Composed of dodecylbenzene, N-methyl-4-piperidone and QBPAF (named QBPAF-10-x , wherein x is the molar ratio of dodecylbenzene to N-methyl-4-piperidone, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out by the following three main steps QBPAF-10-x Similar to QBPAF-1-x: (1) synthesis of poly(aryl-alkylene) polymer, (2) synthesis of alkylated polymer, (3) membrane forging and hydroxide ion exchange. The structural formula is as follows:

[0141]

[0142] Embodiment 11

[0143] Poly(aryl-alkylene) was prepared from dodecylbenzene, N-methyl-4-piperidone and QBPAF (named QBPAF-11-x, where x is the molar ratio of dodecylbenzene to N-methyl-4-piperidone, which is 1 to 100). The preparation was carried out through the following three main steps: QBPAF-11-xSimilar to QBPAF-1-x: (1) synthesis of poly(aryl-alkylene) polymer, (2) synthesis of alkylated polymer, (3) membrane forging and hydroxide ion exchange. The structural formula is as follows:

[0144]

[0145] Example 12

[0146] Composed of dodecylbenzene, N-methyl-4-piperidone and QBPAF (named QBPAF-12-x , wherein x is the molar ratio of dodecylbenzene to N-methyl-4-piperidone, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out by the following three main steps QBPAF-12-x Similar to QBPAF-1-x: (1) synthesis of poly(aryl-alkylene) polymer, (2) synthesis of alkylated polymer, (3) membrane forging and hydroxide ion exchange. The structural formula is as follows:

[0147]

[0148] Example 13

[0149] Poly(aryl-alkylene) was prepared from 1-bromo-3-phenylpropane, trifluoroacetophenone and QBPAF (designated as QBPAF-13-x, where x is the molar ratio of 1-bromo-3-phenylpropane to trifluoroacetophenone, which is 1 to 100). The preparation of QBPAF-13-x is similar to QBPAF-1-x by the following three main steps: (1) synthesis of poly(aryl-alkylene) polymer, (2) synthesis of alkylated polymer, and (3) membrane forging and hydroxide ion exchange. The structural formula is as follows:

[0150]

[0151] Embodiment 14

[0152] The product is composed of 1-bromo-3-phenylpropane, 3-oxo-6-azaspiro[5.5]undecane salt and QBPAF (named QBPAF-14-x , wherein x is the molar ratio of 1-bromo-3-phenylpropane to 3-oxo-6-azaspiro[5.5]undecane salt, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out by the following three main steps QBPAF-14-x :(1) Synthesis of poly(aryl-alkylene) polymer, (2) Synthesis of alkylated polymer, (3) Forging membrane and hydroxide ion exchange. The structural formula is as follows:

[0153]

[0154] Embodiment 15

[0155] Poly(aryl-alkylene) was prepared from 1-bromo-3-phenylpropane, azospirane salt and QBPAF (named QBPAF-15-x, where x is the molar ratio of 1-bromo-3-phenylpropane to azospirane salt, which is 1 to 100). The preparation was carried out through the following three main steps: QBPAF-15-x :(1) Synthesis of poly(aryl-alkylene) polymer, (2) Synthesis of alkylated polymer, (3) Forging membrane and hydroxide ion exchange. The structural formula is as follows:

[0156]

[0157] Example 16

[0158] The product is composed of 1-bromo-3-phenylpropane, N-(11-bromoquinoline)-4-piperidone and QBPAF (named QBPAF-16-x , wherein x is the molar ratio of 1-bromo-3-phenylpropane to N-(11-bromodecyl)-4-piperidone, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out by the following three main steps QBPAF-16-x :(1) Synthesis of poly(aryl-alkylene) polymer, (2) Synthesis of alkylated polymer, (3) Forging membrane and hydroxide ion exchange. The structural formula is as follows:

[0159]

[0160] Embodiment 17

[0161] The product is composed of 1-bromo-3-phenylpropane, 4-(3-bromopropyl)-trifluoroacetophenone and QBPAF (named QBPAF-17-x , wherein x is the molar ratio of 1-bromo-3-phenylpropane to 4-(3-bromopropyl)-trifluoroacetophenone, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out by the following three main steps QBPAF-17-x :(1) Synthesis of poly(aryl-alkylene) polymer, (2) Synthesis of alkylated polymer, (3) Forging membrane and hydroxide ion exchange. The structural formula is as follows:

[0162]

[0163] Embodiment 18

[0164] The product is composed of 1-bromo-3-phenylpropane, 5-bromo-1,1,1-trifluoromethyl-2-one and QBPAF (named QBPAF-18-x , wherein x is the molar ratio of 1-bromo-3-phenylpropane to 5-bromo-1,1,1-trifluoromethyl-2-one, which is 1 to 100) to prepare poly(aryl-alkylene). The preparation is carried out in the following three main steps QBPAF-18-x :(1) Synthesis of poly(aryl-alkylene) polymer, (2) Synthesis of alkylated polymer, (3) Forging membrane and hydroxide ion exchange. The structural formula is as follows:

[0165]

[0166] Comparative Example 1

[0167] Poly(aryl-alkylene) was prepared from 5-bromo-1,1,1-trifluoromethyl-2-ketone and straight terphenyl (named PTP-1). PTP-1 was prepared by the following three main steps: QBPAF-1-x Similar: (1) Synthesis of poly(aryl-alkylene) polymers, (2) Synthesis of alkylated polymers, (3) Forging membranes and hydroxide ion exchange. The structural formula is as follows:

[0168]

[0169] Example 1 (QBPAF-1-85), Example 2 (QmTPAF-2-90) , Example 3 (QBPAF-3-40) The comparison results show the beneficial effects of the present invention:

[0170] Test items Example 1 Example 2 Example 3 Comparative Example 1 80℃ Hydroxide conductivity (mS / cm) 151 153 161 148 Mechanical properties (tensile strength MPa / elongation at break %) 45 / 68 48 / 83 44 / 79 39 / 44 <![CDATA[Battery cell (maximum current density A / cm 2 )]]> 0.8 0.8 0.8 0.8 25℃ Chloride ion conductivity (mS / cm) 11.62 12 12.1 13.06 Methanol solubility Soluble Soluble Soluble Slightly soluble

[0171] In the present invention, due to the introduction of block structure fluorinated aromatic hydrocarbons, the chloride ion conductivity of the polymer of the structural unit of Example 1 is significantly lower than that of the polymer of the structural unit of Comparative Example 1, but it still has the same current density as the polymer of the structural unit of Comparative Example 1 in the water electrolysis unit.

[0172] In the present invention, due to the introduction of block structure fluorinated aromatic hydrocarbons, the membrane undergoes good phase separation. The chloride ion conductivity of the structural unit polymer of Example 1 is significantly lower than that of the structural unit polymer of Comparative Example 1, but it still has a hydroxide ion conductivity similar to that of the structural unit polymer of Comparative Example 1 at 80°C.

[0173] Since similar cation exchange groups are used in both, their alkaline stability is similar.

[0174] The mechanical properties of the block structure fluorinated aromatic hydrocarbons designed in the present invention are significantly better than those of ordinary aromatic hydrocarbon polymers, and the adaptability to the working environment is stronger.

[0175] The block structure designed in the present invention can effectively increase its solubility and can be dissolved in methanol or methanol / water after being soaked in sodium chloride.

[0176] Comparative Example 2

[0177] As an example, a method for synthesizing a monomer of formula (2A) (named QBPAF) is provided:

[0178] During the synthesis of the monomer of the structural formula (2A), the molar ratio of the aromatic hydrocarbon compound to the trifluoroketone monomer is between 2 and 10, and the trifluoroketone monomer is added dropwise to the aromatic hydrocarbon compound.

[0179] In a 50ml single-necked flask, 7.7g (5eq) of biphenyl was dissolved in 10ml of DCM, and the temperature was cooled to 0°C with stirring. TFSA (7.96ml) was slowly added dropwise under temperature control; 1.26g (1eq) of trifluorobutanone was slowly added dropwise (the addition time was about 2h). After the addition was completed, the mixture was reacted at 0°C for 4h.

[0180] After the reaction was completed, methanol aqueous solution (1 / 1) was added, the liquid was separated, the aqueous phase was extracted once with DCM, and the organic phase was washed twice with saturated sodium bicarbonate solution. Drying with anhydrous sodium sulfate. After treatment, column chromatography was performed to obtain 3.12 g of the product, with a yield of about 75.2% (see below). Figure 1 , Figure 2 ).

[0181]

[0182] For comparison, in a 50 ml single-necked flask, 1.54 g (1 eq) of biphenyl was dissolved in 10 ml of DCM, cooled to 0°C with stirring, and TFSA (7.96 ml, 9 eq) was slowly added dropwise under temperature control; 1.26 g (1 eq) of trifluorobutanone was slowly added dropwise (the addition time was about 2 h), and after the addition was completed, the mixture was reacted at 0°C for 4 h.

[0183] After the reaction was completed, methanol-water solution (1 / 1) was added, the liquids were separated, the aqueous phase was extracted once with DCM, and the organic phase was washed twice with saturated sodium bicarbonate solution and dried over anhydrous sodium sulfate to obtain a high molecular weight polymer (reaction as follows).

[0184]

[0185] Comparative Example 3

[0186] In a 50ml single-necked flask, 3.08g (2eq) biphenyl was dissolved in 10ml DCM, cooled to 0°C with stirring, and TFSA (7.96ml) was slowly added dropwise under temperature control; 1.26g (1eq) trifluorobutanone was slowly added dropwise (addition time was about 2h), and after completion of the addition, the mixture was reacted at 0°C for 4h.

[0187] After the reaction was completed, methanol-water solution (1 / 1) was added, the aqueous phase was extracted once with DCM, and the organic phase was washed twice with saturated sodium bicarbonate solution and dried over anhydrous sodium sulfate. After treatment, the product was separated by column chromatography to obtain 1.66 g, with a yield of about 40%.

[0188]

[0189] Comparative Example 4

[0190] For comparison, in a 50 ml single-necked flask, 7.7 g (5 eq) of biphenyl and 1.26 g (1 eq) of trifluorobutanone were dissolved in 10 ml of DCM, cooled to 0°C with stirring, and TFSA (7.96 ml, 9 eq) was slowly added dropwise under temperature control; after the addition was completed, the mixture was reacted at 0°C for 4 h.

[0191] After the reaction was completed, methanol-water solution (1 / 1) was added, the liquids were separated, the aqueous phase was extracted once with DCM, the organic phase was washed twice with saturated sodium bicarbonate solution, dried over anhydrous sodium sulfate, and separated by column chromatography to obtain 1.06 g (35.6%) of the product.

[0192]

[0193] The synthesis process parameters and yields of the monomer of structural formula (2A) in the above Example 1 and Comparative Examples 2 to 4 are shown in the following table:

[0194]

[0195] It can be seen from Example 1 and Comparative Examples 2 and 3 that the molar ratio of the aromatic monomer to the trifluoroketone monomer can affect the yield of the target product. The lower the molar ratio, the easier it is to generate a linear polymer.

[0196] It can be seen from Example 1 and Comparative Example 4 that different process conditions also affect the yield of the target product.

[0197] Compared with the poly (aryl-piperidine) polymer of CN118546339A, the aromatic structure monomer of formula (2A) in this invention is more difficult to synthesize and has a lower yield, which is manifested in that the synthesis process of the aromatic structure of formula (2A) is a polymer polymerization process, which will produce a block structure with a higher molecular weight. In order to increase the yield, the present invention increases the molar mass of aromatic hydrocarbons to ensure that no polymer polymerization reaction occurs, and changes the process conditions, and its yield can reach more than 70%.

[0198] The test method in the above example is as follows:

[0199] 1) Conductivity: The OH- ion conductivity of the fully wet anion exchange membrane in pure water was measured using a four-electrode AC impedance method. The specific test parameters are as follows: a membrane material with an area of ​​5 mm × 10 mm and a thickness of 40 μm was taken, and an AC impedance test was performed at a frequency of 1 Hz to 1000 kHz using a Chenhua (CHI760E) electrochemical workstation. The ionic conductivity was calculated by fitting the curve, and the test temperature was 20 to 100 °C.

[0200] 2) Water absorption rate: The test method refers to the water absorption rate method of proton exchange membrane GB / T 20042.3-2022.

[0201] 3) Mechanical properties: The test method refers to the proton exchange membrane GB / T 20042.3-2022 mechanical properties test method.

[0202] 4) Glass transition temperature (Tg): Differential scanning calorimetry (DSC) was performed using TA Instruments Q20 in a nitrogen atmosphere with a scanning temperature of 20 to 400°C and a heating rate of 10°C / min.

[0203] 5) Electrolyzer unit test: When the cation exchange ionomer in the cathode and anode catalyst layers of the electrolyzer is loaded with 20%, when the voltage is 1.7V constant voltage, the catalyst is: 1mg / cm2 nickel foam on the anode, 0.5mg Pt-C / cm2 on the cathode, the test conditions are electrolyzer temperature and water temperature of 80°C, and the test current density.

[0204] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A polyelectrolyte material, characterized in that the polyelectrolyte material has the following structural units: 1) The structural unit shown in the structure of the following formula 1A: 2) The structural unit shown in the following formula 2A: 3) any structural unit represented by the following formula 3A, 3B, 3C or 3D: Wherein, m represents an integer between 1 and 20; n represents an integer between 0 and 5; b represents an integer between 0 and 5; The R1 groups are independently oxygen, nitrogen, sulfur, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with fluoride; The R 200 , R 210 , R 220 The groups are each independently hydrogen, fluorine, fluoride, alkyl, cycloalkyl, alkenyl, alkynyl or aryl, and the alkyl, cycloalkyl, alkenyl, alkynyl or aryl is optionally substituted with fluoride; The R 100 The group is hydrogen, fluoride, alkyl, cycloalkyl, alkenyl, alkynyl, aryl or a cation exchange group and the alkyl, cycloalkyl, alkenyl, alkynyl or aryl is optionally substituted with fluoride; The R 20 , R 30 , R 40 , R 50 , R 60 , R 70 , R 80 and R 90 The groups are each independently hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide, and wherein R 30 and R 60 an optionally attached halide or alkyl substituted five- or six-membered ring; The R2 groups are independently hydrogen, fluoride, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with fluoride; The R groups are independently alkyl, alkenyl, alkynyl or a substituent having the following formula 4B, and the alkyl, alkenyl, alkynyl or a substituent having the following formula 4B is optionally substituted with a halide or a cation exchange group; The R 110 , R 120 , R 130 , R 140 and R 150 The groups are each independently hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide; The R3 and R4 groups are each independently hydrogen, fluoride, alkyl, alkenyl, alkynyl, aryl or cation exchange group, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with fluoride; The R5 group is an alkyl group, an alkenyl group or an alkynyl group, and the alkyl group, the alkenyl group or the alkynyl group is optionally substituted by a halide group or a cation exchange group.

2. The polyelectrolyte material according to claim 1, characterized in that The cation exchange group has the following structure: Among them, R 11 and R 12 The groups are each independently alkylene; R6, R7, R8, R9 and R 10 The groups are each independently alkyl, alkenyl, aryl or alkynyl; a is 0, 1, 2, 3, 4, 5 or 6; Z is an N element or a P element; The R' group is a nitrogen-containing heterocycle selected from substituted pyrrole, pyrroline, pyrazole, pyrazoline, imidazole, imidazoline, triazole, pyridine, triazine, pyrazine, pyridazine, pyrimidine, azepine, quinoline, piperidine, pyrrolidine, pyrazolidine, imidazolidine, azepane, isoxazole, isoxazoline, oxazole, oxazoline, oxadiazole, oxatriazole, dioxazole, oxazine, oxadiazine, isoxazolidine, morpholine, thiazole, isothiazole, oxathiazole, oxathiazine or caprolactam, wherein each substituent is independently alkyl, alkenyl, alkynyl, aryl or aralkyl.

3. The polyelectrolyte material according to claim 2, characterized in that The R' group is a structure shown in Formula 4A: Where: R 14 , R 15 , R 16 and R 17 Each group is independently hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide.

4. The polyelectrolyte material according to claim 3, characterized in that The R' group has a structure shown in Formula 5 or Formula 5B below:

5. The polyelectrolyte material according to any one of claims 1 to 4, characterized in that The X - For the anion Br - ,I - , Cl - OH - or HCO3 - .

6. The polyelectrolyte material according to claim 1, characterized in that The synthesis method of the structural unit shown in Formula 2A comprises the following steps: dissolving the aromatic hydrocarbon raw material in dichloromethane, stirring and cooling to -5 to 0°C, adding TFSA solution; slowly adding the structural monomer of Formula 3 and reacting for 2 to 72 hours; The structural monomer shown in formula 3 is: The aromatic hydrocarbon raw material is selected from the following structures: n represents an integer between 0 and 5; The R 20 , R 30 , R 40 , R 50 , R 60 , R 70 , R 80 and R 90 The groups are each independently hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide, and wherein R 30 and R 60 an optionally attached halide or alkyl substituted five- or six-membered ring; The R groups are independently alkyl, alkenyl, alkynyl or a substituent having the following formula 4B, and the alkyl, alkenyl, alkynyl or a substituent having the following formula 4B is optionally substituted with a halide or a cation exchange group; The R 110 , R 120 , R 130 , R 140 and R 150 Each group is independently hydrogen, halide, alkyl, alkenyl, alkynyl or aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide.

7. The polyelectrolyte material according to claim 6, characterized in that The molar ratio of the total amount of the aromatic hydrocarbon raw material to the monomer of formula 3 is 2 to 10.

8. The polyelectrolyte material according to claim 6, characterized in that The molar amount of the monomer of formula 3 added per hour is 0.2 to 1 part of the total amount of the aromatic hydrocarbon raw materials added.

9. The polyelectrolyte material according to claim 1 or 6, characterized in that The preparation method of the polyelectrolyte material is as follows: a monomer of a structural unit of formula 1A, a monomer of a structural unit of formula 2A, and a monomer of a structure shown in formula 3 are subjected to a superacid FC reaction under a catalyst to obtain a first intermediate polymer, and the first intermediate polymer is subjected to an alkylation reaction to obtain the polyelectrolyte material.

10. An anion exchange membrane, characterized in that: The polyelectrolyte material according to any one of claims 1 to 9 is dissolved in a polar solvent, cast on a substrate, and exchanged with anions to obtain the polyelectrolyte material.

Citation Information

Patent Citations

  • Polyelectrolyte material, preparation method thereof and alkaline polyelectrolyte membrane

    CN112940226A

  • Polymers having stable cationic pendant groups for use as anion exchange membranes

    CN114025957A

  • Polyaryl piperidine electrolyte material containing fluorocarbon main chain and application of polyaryl piperidine electrolyte material

    CN118546339A